2020
DOI: 10.1057/s41253-020-00121-x
|View full text |Cite
|
Sign up to set email alerts
|

Nationalist and cosmopolitan approaches to the nation: a citizen’s perspective and its electoral impact

Abstract: Whether it is about Québec independence, French language or immigration, nationalism is a crucial feature of Québec politics. The Québec 2018 election is not an exception. Scholars have developed theories about individual identity, the nation and nationhood, but we lack a citizens' perspective. We provide the first thorough description of Quebeckers' nationalism, which reveals a roughly normal (i.e. nonpolarized) distribution of ethnic nationalism attitudes. Most importantly, we measure ethnic nationalism with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…Instead, results were in line with a two-dimensional – civic and ethnocultural – NIR structure (see the Online appendix). A similar factor structure emerged when we analysed this scale for each sample separately (other studies reported similar findings, i.e., Cossette-Lefebvre and Daoust, 2020; Reeskens and Hooghe, 2010; Violante et al, 2020). Consequently, we used an ethnocultural NIR scale (in place of the pre-registered cultural scale) composed of five items averaged into a single score (Wave 1 Cronbach's α = .79; Wave 2 Cronbach's α = .82).…”
Section: Methodssupporting
confidence: 72%
See 2 more Smart Citations
“…Instead, results were in line with a two-dimensional – civic and ethnocultural – NIR structure (see the Online appendix). A similar factor structure emerged when we analysed this scale for each sample separately (other studies reported similar findings, i.e., Cossette-Lefebvre and Daoust, 2020; Reeskens and Hooghe, 2010; Violante et al, 2020). Consequently, we used an ethnocultural NIR scale (in place of the pre-registered cultural scale) composed of five items averaged into a single score (Wave 1 Cronbach's α = .79; Wave 2 Cronbach's α = .82).…”
Section: Methodssupporting
confidence: 72%
“…For instance, Aichholzer et al (2021) found that national identity was not automatically associated with anti-EU attitudes, but this relationship depended on how national identity was conceptualised . Similarly, studies revealed that strongly identifying with exclusionary (versus inclusive) national identities influenced outgroup prejudice, preference for restrictive immigration and asylum policies, and voting for more conservative parties (e.g., Citrin and Wright, 2009; Cossette-Lefebvre and Daoust, 2020; Reijerse et al, 2015). Taken together, these studies suggest that national identity strength alone does not explain attitude outcomes, but national identity content or representations play a cardinal role.…”
Section: National Identity Representations and Euroscepticismmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this remains difficult to accept for those who subscribe to the distinction that is often made between political/civic and cultural/ethnic forms of nationalism (Cossette‐Lefebvre & Daoust, 2020; Keating, 2001; Tamir, 2019). The rights and obligations associated with citizenship are necessarily exclusive insofar as they are framed by the state which is itself being historically rooted in the preferences of ‘nationals’ that have developed over time.…”
Section: Three Observations On Sub‐sate Minority Nationalism: Belongi...mentioning
confidence: 99%